The thalamus and basal ganglia are smaller in children with epilepsy after perinatal stroke - Vaher, Ulvi; Ilves, Norman; Ilves, Nigul; Laugesaar, Rael; Männamaa, Mairi; Loorits, Dagmar; Kool, Pille; Ilves, Pilvi (Frontiers in Neurology, 2023)
Background Epilepsy is one of the most serious consequences of perinatal stroke. Epilepsy itself has been proposed as a risk factor for impaired cognitive, language, and behavioral functioning. It is still unclear which children develop epilepsy after perinatal stroke. The current study aimed to evaluate the volume of the thalamus and the basal ganglia in children after perinatal stroke in relation to poststroke epilepsy. Methods The follow-up study included 29 children with perinatal arterial ischemic stroke (AIS), 33 children with presumed periventricular venous infarction (PVI), and 46 age- and sex-matched healthy controls. Magnetic resonance imaging was performed in children between the ages of 4 and 18 years, and volumetric analysis by segmentation was used to evaluate the size of the thalamus, caudate nucleus, putamen, globus pallidus, hippocampus, amygdala, and nucleus accumbens. Results During a median follow-up time of 12.8 years [interquartile range (IQR): 10.8–17.3] in the AIS group and 12.5 years (IQR: 9.3–14.8) in the PVI group (p = 0.32), epilepsy developed in 10 children (34.5%) with AIS and in 4 (12.1%) children with PVI, p = 0.036 [odds ratio (OR) = 3.8, 95%, confidence interval (CI): 1.04–14]. Epilepsy and interictal epileptiform discharges (IEDs) without clinical seizures were more often expressed in children with AIS (n = 16, 55%) than in children with PVI (n = 7, 21.2%), p = 0.0057 (OR = 3.8 95% CI: 1.04–14). In the AIS group, the ipsilesional and contralesional thalamus, ipsilesional caudate nucleus, and nucleus accumbens were significantly smaller in children with epilepsy compared to children without epilepsy. In the PVI group, the ipsilesional thalamus, caudate nucleus, and nucleus accumbens were smaller in the pooled group of epilepsy plus IED alone compared to children without epilepsy. Conclusion In children with AIS, epilepsy or IED occurred more often compared to children with PVI. Both patients with AIS and PVI with severe damage to the basal ganglia and the thalamus have a higher risk of developing poststroke epilepsy and should be monitored more closely throughout childhood to initiate timely antiseizure medication and rehabilitation.